Russell the sheep - Scotton, Rob. (New York : Harper, 2005)
Russell the sheep tries all different ways to get to sleep.
Publisher's Weekly
School Library Journal
Wilson's Children
Booklist, August 2005
Bulletin (Center for Children's books), May 2005
Horn Book, October 2005
Keywords: Bedtime -- Juvenile fiction; Counting -- Juvenile fiction; Sheep -- Juvenile fiction; Sleep -- Juvenile fiction; Bedtime -- Fiction; Counting -- Fiction; Sheep -- Fiction; Sleep -- Fiction; Bedtime -- Fiction; Counting -- Fiction; Sheep -- Fiction; Sleep -- Fiction; Picture books for children